WHAT WE HAVE LOST FROM WHAT HAVE BEEN DONE: ETHICAL PROBLEMS OF THE SALVAGED SHIPWRECK CARGOES IN INDONESIA - Hutomo Putra (Balai Arkeologi Yogyakarta, 2019)
The struggling in the ethical issues of submerged underwater sites and underwater cultural heritage have been undertaking in Indonesia for the last two decades. During these 20 years, commercial companies in collaboration with the National Shipwreck Committee recovered and salvaged substantial numbers of material cargoes. Unfortunately, the majority of these operations occurred without the involvement of archaeologists and lack of proper and controlled archaeological methods and excavation techniques. Since 2010, the Indonesian Government has declared a moratorium that temporarily stopped all commercial survey and salvage activities, and prohibits the sale of the artefacts. Nowadays, more than 190,000 artefacts raised by salvagers are currently stored at the National Shipwreck Committee warehouses near Jakarta, in Cileungsi, West Java, Indonesia. This study attempts to illustrate the disadvantages of the commercial salvage practices and the auction of salvaged artefacts. This research also discusses some recommendations to contribute to a more ethical system of protection and the long-term management of the Indonesian maritime cultural resources, including its existing collections from salvaged shipwreck sites that are stored at the National Shipwreck Committee warehouse today.